Corporate Social Responsibility Partnership to Alleviate Poverty in Kulon Progo Regency - Ndaru, Felix Aglen; Kurniawan, Teguh (UI Scholars Hub, 2016)
Corporate Social Responsibility (CSR) partnership between the public sector and the private sector has become a new trend in Indonesia in order to overcome budget constraint. However, most CSR programs are not empowering and the LocalGovernments tend to share development burden to the private sector. Kulon Progo Regency is the poorest region in Java Island that conducts a CSR partnership through One Village One Sister Company (OVOSC) program. This study viewed communityempowerment and the discretion of the private sector in OVOSC program. The research approach of this study was the qualitative approach, which utilize in-depth interviews and literature study. Research results show that OVOSC program is dominated bycharity programs. The private companies also have relatively large discretion because the Government tends to share development task to external actors based on the philosophy of gotong royong (mutual cooperation). Kulon Progo Regency Government shouldendorse the companies to launch more empowerment programs and strengthen the monitoring in order to avoid the companies from abusing the discretion. This research also confirms the statement from Donahue and Zeckhauser (2011) that categorized CSRas an alternative way to engage private players in public missions and different from collaborative governance.